Chronic intermittent ethanol promotes ventral subiculum hyperexcitability via increases in extrinsic basolateral amygdala input and local network activity - Eva C. Bach (Nature Portfolio, 2021)
Abstract The hippocampus, particularly its ventral domain, can promote negative affective states (i.e. stress and anxiety) that play an integral role in the development and persistence of alcohol use disorder (AUD). The ventral hippocampus (vHC) receives strong excitatory input from the basolateral amygdala (BLA) and the BLA-vHC projection bidirectionally modulates anxiety-like behaviors. However, no studies have examined the effects of chronic alcohol on the BLA-vHC circuit. In the present study, we used ex vivo electrophysiology in conjunction with optogenetic approaches to examine the effects of chronic intermittent ethanol exposure (CIE), a well-established rodent model of AUD, on the BLA-vHC projection and putative intrinsic vHC synaptic plasticity. We discovered prominent BLA innervation in the subicular region of the vHC (vSub). CIE led to an overall increase in the excitatory/inhibitory balance, an increase in AMPA/NMDA ratios but no change in paired-pulse ratios, consistent with a postsynaptic increase in excitability in the BLA-vSub circuit. CIE treatment also led to an increase in intrinsic network excitability in the vSub. Overall, our findings suggest a hyperexcitable state in BLA-vSub specific inputs as well as intrinsic inputs to vSub pyramidal neurons which may contribute to the negative affective behaviors associated with CIE.